Re-visiting professional ethics in psychotherapy: reflections on the use of talking therapies as a supportive adjunct for myalgic encephalomyelitis/chronic fatigue syndrome and ‘medically unexplained symptoms’ - Hunt, Joanne; Blease, Charlotte (Journal of medical ethics, 2024)
Following years of debate over the effectiveness of cognitive behavioural therapy for myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS), public health bodies in the UK and beyond have determined that no psychotherapy is clinically proven for this patient group. In the field of ME/CFS and the wider arena of ‘medically unexplained symptoms’ (MUS), patient survey data and qualitative research capturing patient experiences and psychotherapist attitudes suggest that therapeutic practice may sometimes fall short of required ethical standards. This raises questions about how psychotherapists can safely support, as opposed to treat, people with these debilitating conditions. We consider four ethical principles that feature throughout psychotherapists’ codes of practice, those of respect, competence, responsibility and integrity, and discuss examples of good and poor practice in this arena as evinced by recent empirical literature. Following this, we offer a variety of suggestions to help strengthen ethical psychotherapy practice with patients with ME/CFS and other MUS. In terms of practitioner education, we recommend greater emphasis on humility, reflexivity and disability-affirming practices, exploration of personal as well professional ethics, and integration of patient expertise-by-experience, accompanied with the latest evidence, into foundational and ongoing training. In terms of ongoing practice, we suggest consideration of formalised patient-focused feedback systems and greater transparency vis-à-vis patient access to clinical notes. Finally, we underline the importance of elevating patients from mere subjects to co-producers of psychotherapy research.